”Alshaikh Amro Al Talati and his methodology in his book “Rafa’a Altrakhi Fi Mukhtasar Al Shamahi - Al Harthy, Ahmed bin Nasser bin Mohammed (Journal of Islamic Sciences, 2019)
The research aims to shed light on the personality of Sheikh Amr Bin Ramadan Al-Talati his birth, origin, life, request for knowledge, and his Authored books. And about his book “Rafa’a Altrakhi Fi Mukhtasar Alshamakhi”in terms of fundamentalist methodology between the schools of jurists and Theologists. The research concludes that Shaikh Amro Bin Ramadan Altalati was born in the island of Jerba in Tunisia at the end of Eleventh Hijri century. He grew up and started to seek for knowledge in there. Then, he traveled to Egypt to continue seeking the knowledge from Egyptian Shaikh’s in Al-Azhar learning center and he excelled in this field and this has set him above others. After that, he started to have his own teaching classes. He passed away in 1187 Hijri leaving huge amount of books and one of the most important one was the “Rafa’a Altrakhi Fi Mukhtasar Alshamakhi”. Which he elaborated the book “Mukhtasar Ketab Aladal Wa Alinsaf” explaining, analyzing, comparing and adding his prospective also. The method he used was Theologists's approach on the basis firstly then adding on it. He also absorbed on it almost of all the fundamental matters.
Keywords: Jurists; Al-Fuqha’a; Theologists; Almutakalmin; Al-Ibadyah; Altalati; Alshamakhi; Principles; usuol